INVENTARISASI TUMBUHAN BAWAH DI KAWASAN HUTAN TAMAN WISATA ALAM SIBOLANGIT, KABUPATEN DELI SERDANG - Puspita Sari, Wina Dyah; Aryeni, Aryeni (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2017)
Underwater plants are plants in the form of herbaceous plants and shrubs and low plants that cover the bottom of a forest area. Thus the function of the plant here is to withstand the destructive power of the falling rain fall and the rapid flow of water above the soil surface. Sibolangit Nature Park is a forest area with an area of Â± 24.85 Ha. The existence of the lower plants in Sibolangit Nature Park become the main attraction for the visitors. The purpose of the research is to obtain the inventory data of the lower plants and describe the characters morphology. The research was conducted by using the exploration method along the path of Sibolangit Nature Park. From the research that has been done, there are 48 types of plants that consist of 31 families. Of the 48 undersea species identified, 30 of them belong to the Spermatophyta division, while the remaining 18 are included in the Pterydophyta division.Underwater plants are plants in the form of herbaceous plants and shrubs and low plants that cover the bottom of a forest area. Thus the function of the plant here is to withstand the destructive power of the falling rain fall and the rapid flow of water above the soil surface. Sibolangit Nature Park is a forest area with an area of Â± 24.85 Ha. The existence of the lower plants in Sibolangit Nature Park become the main attraction for the visitors. The purpose of the research is to obtain the inventory data of the lower plants and describe the characters morphology. The research was conducted by using the exploration method along the path of Sibolangit Nature Park. From the research that has been done, there are 48 types of plants that consist of 31 families. Of the 48 undersea species identified, 30 of them belong to the Spermatophyta division, while the remaining 18 are included in the Pterydophyta division.